Chapter 7. The way forward: recommendations for further actions - Houmy, Karim; Mpagalile, Joseph; Flores Rojas, Mayling; Odjo, Sylvanus (Food and Agriculture Organization of the United Nations, 2024)
In 2014, the African Union (AU) Summit in Malabo set the ambitious goal to halve post-harvest losses by 2025. However, the challenges and complexities of achieving this target have now been realized. With only one year remaining until this deadline, it is evident that post-harvest loss(PHL) remains a pressing issue in Africa, demanding immediate attention and innovative strategies. This publication details the continual challenges that hinder the reduction of post-harvest losses. A critical barrier is the limited access to improved technologies, hindering the adoption of more efficient and modern practices in various stages of the agricultural value chain. In addition, the non-adherence to a comprehensive value chain approach also contributes to the fragmented efforts in addressing post-harvest losses, necessitating a more holistic and interconnected strategy. Furthermore, institutional challenges exacerbate the issue, with many countries lacking clear and robust strategies to confront post-harvest losses effectively. This institutional gap underscores the need for coordinated efforts involving governments, the private sector and civil society to establish and implement comprehensive policies to mitigate losses across the food system. As the AU Malabo summit’s deadline approaches, the persistence of these challenges emphasizes the urgency for renewed commitment and innovative solutions. There is a call for a collaborative approach that engages stakeholders at local, national, and global levels. This involves not only acknowledging the multifaceted nature of post-harvest losses but also actively seeking innovative solutions that address the root causes whilst promoting sustainable food security for the African continent. This publication has shown that despite the ongoing efforts to reduce PHL, it remains a significant challenge for many smallholder farmers in Africa. Several gaps that contribute to increases in post-harvest losses among farmers, especially smallholders, have been identified and recommendations that contribute to the reduction of PHL have been demonstrated and showcased.